Incidence of Severe Postpartum Hemorrhage and Factors Influencing Labor Induction in Patients with Hypertension and Non-Severe Preeclampsia during Full-Term Pregnancy - Yili Song; Maoling Yin; Yinghua Yu; Rong Xu (Clinical and Experimental Obstetrics & Gynecology)
Background: At present, postpartum hemorrhage (PPH) is still one of the main causes of global incidence rate and mortality of pregnant women, especially in term pregnancy with hypertension. Among them, non-severe preeclampsia is increasingly considered to have the potential to lead to adverse maternal outcomes, including severe postpartum hemorrhage. This study aims to conduct a survey on the incidence of severe PPH in patients with hypertension and non-severe preeclampsia during full-term pregnancy, and analyze the factors influencing severe PPH in these patients. Methods: This retrospective study analyzed 300 full-term patients with gestational hypertension and non-severe preeclampsia who underwent labor induction at our hospital between November 2021 and November 2023. According to the occurrence of severe postpartum hemorrhage, patients were divided into two groups: 250 cases in the mild postpartum bleeding group (control group) and 50 cases in the severe postpartum bleeding group (experimental group). The two groups were compared, and statistically significant factors were included in the subsequent analyses to investigate the factors influencing severe PPH in patients with full-term gestational hypertension and non-severe preeclampsia. Results: Intraoperative and 24-hour postoperative hemorrhage were significantly lower in patients with non-severe hemorrhage compared to those with severe hemorrhage (p < 0.05). However, no statistically significant differences were observed between the two groups in several parameters, including the number of births, age, systolic blood pressure, early preeclampsia, diastolic blood pressure, mode of labor induction, hemoglobin levels at admission, gestational age, and newborn body weight (p > 0.05). In contrast, statistically significant differences were observed between the two groups in terms of the use of oxytocin during labor, the mode of delivery, and the duration between labor induction and the onset of delivery (p < 0.05). Furthermore, a lower incidence of postpartum urinary retention was observed in the non-severe hemorrhage group compared to the severe hemorrhage group, with a statistically significant difference (p < 0.05). Logistic regression analysis identified the use of oxytocin during labor, mode of delivery, time between the start of induction and delivery, and postpartum urinary retention as independent factors influencing the incidence of severe PPH in patients with non-severe preeclampsia (p < 0.05). Conclusions: The occurrence of severe PPH in patients with hypertension and non-severe preeclampsia at full-term gestation and labor induction is attributed to the multifactorial effects of vaginal delivery, instrumental delivery, and the use of oxytocin during labor. Proactive and effective management is essential to reduce hemorrhage during labor induction.